MicroRNA-300: A Transcellular Mediator in Exosome Regulates Melanoma Progression - Chen, Long; Karisma, Vega Windy; Liu, Huawen; Zhong, Li (Frontiers in Oncology, 2019)
Melanoma is a common and high-mortality skin cancer. Oxidative stress and DNA damage caused by ultraviolet are major causative factors of melanoma formation. However, the specific molecular mechanism is still unclear. In this study, 218 dysregulated genes and 104 dysregulated miRNAs in response to UV were screened by analyzing sequencing datasets. Among them, 29 up-regulated miRNAs and 28 down-regulated miRNAs were involved in the melanoma pathway. As the only differential gene in the melanoma pathway, GADD45B severely affects the prognosis of melanoma patients. MiR-300 is the only differentially expressed miRNA which regulates GADD45B. In addition, compared to normal melanocytes, miR-300 was significantly down-regulated in melanoma cells (log FC = -1.63) and exosomes (log FC = -1.34). Among the transcription factors predicted to regulate miR-300, MYC, PPARG, and ZIC2 were significantly up-regulated in melanoma cells, and TP53, JUN, JUNB, FOS, and FOSB were interacted with GADD45B. We attempte to reveal the pathogenesis of melanoma and screen new biomarkers by constructing a TF-mRNA-miRNA axis in turn to provide a view for further research.